Performance Of Chromium-Copper On Modified H-ZSM-5 Catalysts In The Combustion Of VOC Pollution In Air. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2005)
The performance of chromium (cr) and copper (cu) on silicon tetrachloride modified H-ZSM-S (SiCl4-Z) catalyst in VoC coflrbustion is reported.